2014
DOI: 10.1186/2193-1801-3-195
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to diabetes medication adherence in North West Ethiopia

Abstract: BackgroundLow adherence to prescribed diabetes medications is one of the major reasons to poor glycemic control in developing countries. Therefore, this study attempted to assess the magnitude of medication adherence and factors associated with it among adult persons with diabetes in northwest Ethiopia.MethodThis study utilized a cross sectional study design with internal comparison. The study population was adult persons with diabetes attending the Diabetes Referral Clinic of Gondar University Hospital. Adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 37 publications
(50 reference statements)
11
72
1
1
Order By: Relevance
“…The finding of this study was similar to study done in Harari 39.3% of the study participants had good self-care practices [48]. However findings from study done in JUSH; 45% of the participants had Good self-care practice [40] and Nekemte Referral Hospital showed that; 45% of study participants had good self-care practices [9].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The finding of this study was similar to study done in Harari 39.3% of the study participants had good self-care practices [48]. However findings from study done in JUSH; 45% of the participants had Good self-care practice [40] and Nekemte Referral Hospital showed that; 45% of study participants had good self-care practices [9].…”
Section: Discussionsupporting
confidence: 76%
“…This is similar with study done in Nekemte Referral Hospital; Subjects earning relatively high average monthly income (750-1050) Birr were 5.6 times more likely to practice self-care than those earning less than 350 Birr [9] and study done in Harari; patients relatively in high income category can get healthy foods that are recommended for diabetic patients [48], high income was correlated with high self-care ability or low income was associated with low self-care ability than those middle and high income patients [91].…”
Section: Diabetes Knowledge Response Responsesupporting
confidence: 77%
See 3 more Smart Citations